2007
DOI: 10.1098/rstb.2007.2201
|View full text |Cite
|
Sign up to set email alerts
|

Spatially explicit fire-climate history of the boreal forest-tundra (Eastern Canada) over the last 2000 years

Abstract: Across the boreal forest, fire is the main disturbance factor and driver of ecosystem changes. In this study, we reconstructed a long-term, spatially explicit fire history of a forest-tundra region in northeastern Canada. We hypothesized that current occupation of similar topographic and edaphic sites by tundra and forest was the consequence of cumulative regression with time of forest cover due to compounding fire and climate disturbances. All fires were mapped and dated per 100 year intervals over the last 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 74 publications
(99 reference statements)
2
45
0
Order By: Relevance
“…This persistence of cold conditions over NENA is also suggested by the strong warming trend of the last 100 y denoting a colder starting point ( Fig. 1 A and B), as well as by permafrost growth during the mid-20th century on the southern shore of Hudson Strait (35) and by the lack of postfire forest recovery over the last 900 y at the northern Quebec treeline in contrast to what occurred during the Medieval Climate Anomaly (36,37). The warming trend in our study area has accelerated over the last 30 y (+0.7°C per decade according to the dataset CRU TS3.20).…”
Section: Resultsmentioning
confidence: 95%
“…This persistence of cold conditions over NENA is also suggested by the strong warming trend of the last 100 y denoting a colder starting point ( Fig. 1 A and B), as well as by permafrost growth during the mid-20th century on the southern shore of Hudson Strait (35) and by the lack of postfire forest recovery over the last 900 y at the northern Quebec treeline in contrast to what occurred during the Medieval Climate Anomaly (36,37). The warming trend in our study area has accelerated over the last 30 y (+0.7°C per decade according to the dataset CRU TS3.20).…”
Section: Resultsmentioning
confidence: 95%
“…Sirén 1961;Zackrisson 1977;Terasmae & Weeks 1979;Tolonen 1983;Pitkänen et al 2002;Ryan 2002;Carcaillet et al 2007;Payette et al 2008;Wallenius et al 2010;Barrett et al 2013;Brown & Giesecke 2014). about one fire in 200 years) appears consistent with the frequency of fires in Fennoscandian and North American boreal forests, which is normally within the range of 1 in 50-250 years (cf.…”
Section: Relating Charcoal Ages To the Timing Of Forest Fires And Colmentioning
confidence: 58%
“…Our results indicate that all the tundra summits studied were created by fire disturbance during the late Holocene, mostly between 100 and 500 cal y BP and 1150-1600 cal y BP. Fire frequency at the northern limit of the forest tundra varied greatly during the last few millennia, but a major reduction of the forest cover occurred during this period, often in a one-shot fire event (Payette, Filion & Delwaide, 2008). Asselin and Payette (2005) have shown that the decrease and clearance of the forest cover in the forest tundra were due to interactions between climate and fire.…”
Section: Discussionmentioning
confidence: 99%